Microplastic Pollution in Surface Waters of Urban Watersheds in Central Texas, United States: A Comparison of Sites With and Without Treated Wastewater Effluent - Stovall, Jasmine K.; Bratton, Susan Power (Frontiers in Analytical Science, 2022)
Most studies of microplastics in freshwater have investigated presence in creeks and rivers below sewage effluents and storm drains. This study examines microplastic distribution in surface waters, including springs and primary streams, located within small, urban Karst watersheds, with and without sources of wastewater treatment discharge. Study locales were in Texas, USA, either in Waco on the Brazos River or in or downstream from San Marcos on the San Marcos River. Research teams collected 800 mL surface water from four different small watersheds and an urban pond (n=779) and filtered them through 53 μm Nitex mesh. Teams collected samples from springs or primary streams to the lower end of creeks and across stream transects based on distance from the bank and the presence of vegetation and debris. Teams also replicated samples seasonally. Stereo microscopy examined each filter for microplastic particles and subsequently color and type (i.e., fragment, fiber, or sphere). Additionally, we analyzed the influence of urbanization and land use on the origin and transport of the microplastics. Overall, the filters recovered 1,198 microplastic fibers and fragments. On average, 56.7% of all samples at each study locale contained microplastics. Particle abundance was the highest at Proctor Springs (x ̅=3.38) and lowest at the pond (x ̅=0.98), both headwaters. Local human use and runoff were thus potentially important factors in microplastic presence, while sewage discharge was not unilaterally the primary determinant of microplastic abundance. Peak pollution events occurred in June, September, and October, indicating seasonality of rainfall and recreation affected microplastic frequency and type.